Health Risk Assessment of Occupational Exposure of Refinery Unit Site Workers to BTEX in an Oil Refinery Company - Samad Jalilian; Sima Sabzalipour; Maryam Mohammadi Rouzbahani; Ebrahim Rajabzadeh Ghatrami; Leila Ibrahimy Ghavamabadi (Shiraz University of Medical Sciences, 2022)
Background: Specific improvements in the risk assessment of chemicals have been recently considered by many national and international expert groups. This study aimed to identify the highest occupational exposure levels in  Abadan Oil Refining Company, Iran, to benzene, toluene, ethylbenzene, and xylene (BTEX) in 2020. Methods: This is a cross-sectional, descriptive and analytical study carried out in several units (ten units) in Abadan Oil Refining Company. Air sampling and BTEX analysis were conducted according to NIOSH method number 1501. To determine the risk of exposure to BTEX pollutants, we used the method proposed by the Department of Occupational Safety and Health of Malaysia. Then, the hazard rate, exposure rate, and health risk level caused by exposure to chemicals were determined. Spss20 software was used to analyze the data. Results: The results showed the employees studied in this research were exposed to the pollutants of BTEX during their work. Comparing total BTEX concentrations with the recommended standard level showed that BTEX concentrations in Abadan Oil Refining Company Workers' breathing zone were lower than the TLV-TWA recommended by ACGIH; also, the findings of this risk assessment study showed benzene had the highest risk ranking in seven operating units and a low risk ranking in three other units. Moreover, toluene, ethylbenzene, and xylene had a very low risk in all operating units. Conclusion: Corrective and preventive measures should be taken to eliminate or minimize the exposure rate due to the significant effects of benzene exposure.